Technological sovereignty and independence. The challenges and risks of “new” intelligence. A system assessment - Romeo, Giuseppe (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
There is no doubt that the approach towards a “new” dimension of intelligence aimed at adding to human possibilities – in an attempt to amplify the capabilities and possibilities of processing behaviour, as well as information – will include and involve the existential sphere of the individual in his dimension as a person as well as in his organized manifestations as a political and economic subject. All this, in the different and new organizational architectures destined to manage, and therefore to govern, every future of the international community and, with it, of all humanity, redetermining new balances of power and new relationships between international political subjects. The challenge to the dominance of superintelligences, in the field of AI as in Quantum Computing, will determine new structures and new modes of governance which will have to correspond to new rules and new strategies aimed at not making international bargaining a dangerous opportunity for power policies aimed at conquering technological supremacy in a model of technopolar international system.